Terror Death of Election Officials: What Are the Effects of Stress and Hypoxia?: A Literature Review - Arif Rahman Nurdianto; Achmad Nurdin Himawan; Anis Dwi Anita Rini; Anita Devi; Hisnindarsyah Hisnindarsyah; Fery Setiawan; Rizal Fauzi Nurdianto (Universitas Wijaya Kusuma Surabaya, 2024)
Background: This essay examines the most recent news, namely the passing of a voting committee member (PPS) in the general election (Pemilu), which included candidates for president, vice president, and legislature (Caleg). PPS saw 35 fatalities and 3.909 illnesses. Given that the counting and recapitulation process is still in progress, the likelihood of deaths and illnesses will only rise. Objective: The aim of this research is to find the relationship between hypoxia and stress in PPS officers who died due to physical exhaustion during election activities in Indonesia Methods: Articles containing information on hypoxia, comorbidity, stress, physical exhaustion, and its connection to death were included as inclusion criteria. There was a total of 25 papers that met the inclusion criteria after the literature analysis procedure was completed. Result: Along with the comorbid status, physical exhaustion, and stress play a significant part (comorbidities). This connection arises from the fact that physical exhaustion and stress induce hypoxia, which in turn affects immunity. The drop in blood oxygen levels, or hypoxia, disrupts and dysregulates the innate and adaptive immune systems. The chance of dying can rise when hypoxia and ongoing stress are present. Writing this paper proposes more investigation into the role that hypoxia and stress play as death risk factors. Conclusion: Hypoxia results from stress. what makes HIF the primary transcription factor active. When PPS officers activate their HIF in order to fulfill their mandate and fulfill their obligations under Law Number 7 of 2017 concerning General Elections, there is an elevated risk of death and morbidity.